A single center experience of concomitant administration of sofosbuvir/velpatasvir and amiodarone after heart and lung transplantation - Ryan M. Rivosecchi; Pablo G. Sanchez; Lauren M. Sacha; Edward T. Horn; Mary Keebler; Fernanda P. Silveira (JHLT Open)
The advent of direct-acting antiviral agents (DAA) allows for the utilization of hepatitis C (HCV) viremic donors to uninfected recipients. Sofosbuvir/velpatasvir (SOF/VEL) is a pangenotypic DAA without clinically significant interactions with immunosuppressants, but its concomitant use with amiodarone may cause serious bradycardia. In an open-label study of 20 heart and lung transplant recipients of organs from HCV viremic donors, who received SOF/VEL for 12 weeks starting on post-operative day one, the concomitant use of amiodarone and SOF/VEL resulted in bradycardic episodes and commonly occurred in the presence of beta-blocking medications. Episodes of bradycardia were transient, resolved with intervention, and did not require the discontinuation of SOF/VEL. In patients requiring the combination of SOF/VEL and amiodarone, consideration of therapeutic options is warranted prior to the addition of other bradycardia-inducing medications.